2010
DOI: 10.1016/j.ijsu.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia rates following laparoscopic colorectal resection

Abstract: The well-documented advantages of laparoscopic surgery include reduced hospital stay, early return to activity, decreased analgesic requirements and improved cosmesis. However, the results of this study suggest that incisional hernia rates are not decreased by laparoscopic surgery, although the hernias may be smaller and more amenable to repair by laparoscopic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…The literature review identified 17 original articles concerning ventral incisional hernia after laparotomy [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], 17 original articles concerning ventral incisional hernia after laparoscopy [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39] and 17 comparative studies of laparotomy vs. laparoscopy [3,38,[40][41][42][43][44][45][46][47][48][49][50][51][52][53]…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review identified 17 original articles concerning ventral incisional hernia after laparotomy [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], 17 original articles concerning ventral incisional hernia after laparoscopy [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39] and 17 comparative studies of laparotomy vs. laparoscopy [3,38,[40][41][42][43][44][45][46][47][48][49][50][51][52][53]…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…Incisional hernia can develop either at the incisional site through which the specimen is extracted, or even at trocar sites. In a compilation of 16 published reports (Table 3) over the last 10 years and including 20,281 patients, the reported rate of incisional hernia from all sites is 0.7%; 0.4% occur at trocar sites and 0.3% at the incision for specimen extraction [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39]. The risk seems to be less for upper abdominal surgery with a minimum rate of 0.1% reported by Duca et al in a prospective study of 9542 cholecystectomies [23].…”
Section: Ventral Incisional Hernia After Laparoscopymentioning
confidence: 99%
“…2 Incisional hernia incidence after elective midline incision, e.g., for the oncologic resection of colorectal cancer, is high with reported 10–40%. 3, 4 Most incisional hernias develop within 2 years after surgery 5 and can cause severe health and cosmetic problems. Each year, over 340,000 hernia repairs are performed in the United States, causing health care costs of at least $3.2 billion.…”
Section: Introductionmentioning
confidence: 99%
“…These hernias follow previous abdominal wall surgery and are common with midline incisions and, rarely, laparoscopic port1 sites or ambulatory peritoneal dialysis cannula sites 2…”
Section: Introductionmentioning
confidence: 99%
“…Poor surgical technique and post operative wound infection are contributory. Midline scars are particularly vulnerable because of the poor healing properties of fascial tissue 14. Obesity, size of defect,7 advanced age, prolonged use of steroids, malnutrition, uraemia, diabetes, jaundice and raised intra-abdominal pressure from any cause are other known risk factors 489…”
Section: Introductionmentioning
confidence: 99%